Collateral, Liquidity and Debt Sustainability - Stefan Niemann; Paul Pichler (Oesterreichische Nationalbank (OeNB), 2013)
We study the sustainability of public debt in a closed production economy where a benevolent government chooses scal policies, including haircuts on its outstanding debt, in a discretionary manner. Government bonds are held by domestic agents to smooth consumption over time and because they provide collateral and liquidity services. We characterize a recursive equilibrium where public debt amounts to a sizeable fraction of output in steady state and is nevertheless fully serviced by the government. In a calibrated economy, steady state debt amounts to around 84% of output, the government's default threshold is at around 94% of output, and the haircut on outstanding debt at this threshold is around 40%. Both reputational costs of default and contemporaneous costs due to lost collateral and liquidity are essential to generate these empirically plausible predictions.
Keywords: E44; E62; H21; H63; 330; sustainability; nancial frictions; sovereign default; domestic debt; endogenous haircut